Pengetahuan, Persepsi dan Sikap Tentang Obat Pada Siswa SMK Muhammadiyah Susukan Kabupaten Semarang - Fitria Nugrahaeni; Miatin Rachmawati (Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2021)
An irrational use of drug and drug abuse are some of the impacts of the low knowledge of the public about medicine, including vocational students. This study aimed to assess the knowledge, perceptions, and attitudes of Muhammadiyah Susukan high school (SMK) students about medicine. The research was conducted by using descriptive and analytical methods with cross sectional using a questionnaire instrument. This research was conducted in June 2020. Data were analyzed using univariate and bivariate analysis. The results obtained indicate that students' perceptions of drug safety are 76.7%, students have a positive attitude with drugs 91.7%, but have less knowledge (50.6%). The place where respondents live in the village has a close relationship with their level of the knowledge. There is a relationship between perception and attitude (P 0.05) but there is no relationship between knowledge and perception (P 0.05), and between knowledge and attitude (P 0.05). Low levels of knowledge and perceptions can cause students to abuse drugs or use drugs that are not rational. So that efforts are needed to increase students' knowledge about medicine.Keywords: knowledge, perceptions, attitudes about medicine, students